Antibacterial and antifungal activities of 2, 3-pyrrolidinedione derivatives against oral pathogens. Issue 5 (1st March 2016) - Dhavan, Atul A.; Ionescu, Andrei C.; Kaduskar, Rahul D.; Brambilla, Eugenio; Dallavalle, Sabrina; Varoni, Elena Maria; Iriti, Marcello
Graphical abstract: Abstract: Among the novel approaches applied to antimicrobial drug development, natural product-inspired synthesis plays a major role, by providing biologically validated starting points. Tetramic acids, a class of natural products containing a 2, 4-pyrrolidinedione ring system, have attracted considerable attention for their antibacterial, antiviral, antifungal and anticancer activities. On the contrary, compounds with a 2, 3-pyrrolidinedione skeleton have been considerably less investigated. In this work, we established chemical routes to the substituted 2, 3-pyrrolidinedione core, which enabled the introduction of a wide range of diversity. In the perspective of a potential application for oral healthcare, a number of analogues with various substituents on the 2, 3-pyrrolidinedione core were investigated for their antimicrobial and antifungal activities. The most promising compound showed a significant antimicrobial activity on Streptococcus mutans and Candida albicans, comparable to that of chlorhexidine, the gold standard in oral healthcare.